Revolutionizing Form and Function: Exploring 4D Printing as a Novel Manufacturing Approach for Complex Generative Structures and Customized Formworks - Vinay Kumar Agrahari (International Journal of Manufacturing and Production Engineering, 2024)
This research delves into the transformative potential of 4D printing manufacturing technology, focusing on its innovative application in fabricating intricate generative and computational structures for adaptable formwork in both individualized and mass-customized scenarios. Spanning the interdisciplinary realms of digital design, digital fabrication, and material science, the study comprehensively explores the integration of these diverse fields. Utilizing generative algorithms and parametric design tools, the research employs simulations to realize complex patterns inspired by the curved-crease technique of origami art. Conceptualizing 4D printing as a groundbreaking technique, the study emphasizes its capacity to create responsive formworks with structural integrity across diverse scenarios. The key innovation lies in synthesizing generative structures that maintain their form through the same printed entities, enabling the development of self-folding active composite structures adaptable to changing environmental conditions. The experimental journey involves a series of design and fabrication exercises, combining digital simulations with hands-on practices, including the adaptation of desktop FDM printers and widely available thermoplastic filaments. Challenges related to scale, material choice, and printer capabilities are addressed, culminating in a demonstration showcasing 4D printing's potential in generating active composite structures suitable for both formwork and structural applications. While architectural-scale applications may be a longer-term aspiration, the study's outcomes open promising avenues for future research, highlighting the prospect of creating dynamic, self-responsive structures that redefine the intersection of technology and design.
Keywords: Additive manufacturing; Exploring the synergy of formwork; and 4D printing constitutes the core of this research endeavor; curved-crease folding; digital fabrication